Characterizing Biology Education Research: Perspectives from Practitioners and Scholars in the Field - Jeremy L. Hsu (American Society for Microbiology, 2021)
ABSTRACT Biology education research (BER) is a recently emerging field mainly focused on the learning and teaching of biology in postsecondary education. As BER continues to grow, exploring what goals, questions, and scholarship the field encompasses will provide an opportunity for the community to reflect on what new lines of inquiry could be pursued in the future. There have been top-down approaches at characterizing BER, such as aims and scope provided by professional societies or peer-reviewed journals, and literature analyses with evidence for current and historical research trends. However, there have not been previous attempts with a bottom-up approach at characterizing BER by directly surveying practitioners and scholars in the field. Here, we share survey results that asked participants at the Society for the Advancement of Biology Education Research (SABER) annual meeting what they perceive as current scholarship in BER as well as what areas of inquiry in the field that they would like to see pursued in the future. These survey responses provide us with information directly from BER practitioners and scholars, and we invite colleagues to reflect on how we can collectively and collaboratively continue to promote BER as a field.